Simultaneous determination of anti-diabetic drugs - Nawab Sher; Nasreen Fatima; Shahnaz Perveen; Farhan Ahmed Siddiqui (Universidade de São Paulo, 2019)
A novel reverse phase, isocratic HPLC method is described to separate five anti-diabetic drugs i.e., glimepiride, metformin, sitagliptin, rosiglitazone and pioglitazone. Nucleosil C18 analytical column was used as stationary phase, while mobile phase consisted of acetonitrile:phosphate buffer: methanol (40/40/20, v/v) pH 2.0. Effluent was monitored at a flow rate 1 mL/min and detected at wavelength of 240 nm. This research produced excellent chromatography over a wide concentration range of 25-10000 ng/mL. Sepprated and well resolved quantifiable peaks were obtained and test results were linear in this range. Correlation coefficient of more than 0.9990 was witnessed as well as Low %RSD values i.e., maximum 2.0% documented excellent precision of the method. Good recoveries from pharmaecutical (99-101%), urine and plasma samples (>96%) in a range of concentrtion granted very good linearity, accuracy and precision. The projected method has satisfactory applications in quality control of these molecules as well as quantification of these molecules in urine and plasma samples.